2008
DOI: 10.1177/153303460800700503
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Streamlined, Non-invasive Robotic Radiosurgery Method for Treatment of Uveal Melanoma

Abstract: To analyze the feasibility and safety of frameless, image-guided robotic radiosurgery against uveal melanoma, we developed a streamlined procedure that is completed within 3 hours under retrobulbar anesthesia without immobilization. Twenty patients (10 men and 10 women) with medium (3-5-mm prominence) and large (>5-mm prominence) unilateral uveal melanomas were treated with a frameless robotic radiosurgery system. Median age was 61 years (range 32-78 years). All patients underwent a single-session procedure be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0
10

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 27 publications
1
32
0
10
Order By: Relevance
“…Hirasawa et al [29] have identified the anterior segment of the eye and the optic disc as structures of great risk for neovascular glaucoma based on a multivariate analysis, and recommended irradiation techniques that would spare these structures as much as possible when treating uveal melanoma. The high flexibility of the robotic technology used in the current study is capable of achieving this goal [2,3,10]. Although these data cannot be directly correlated to visual outcome, it clearly documents the ability of the robotic system to adjust the dose to the tumor as much as possible by maximally sparing the sensitive structures of the eye from the dose.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Hirasawa et al [29] have identified the anterior segment of the eye and the optic disc as structures of great risk for neovascular glaucoma based on a multivariate analysis, and recommended irradiation techniques that would spare these structures as much as possible when treating uveal melanoma. The high flexibility of the robotic technology used in the current study is capable of achieving this goal [2,3,10]. Although these data cannot be directly correlated to visual outcome, it clearly documents the ability of the robotic system to adjust the dose to the tumor as much as possible by maximally sparing the sensitive structures of the eye from the dose.…”
Section: Discussionmentioning
confidence: 87%
“…This was the cutoff used for follow-up of visual function. All patients underwent a standardized outpatient procedure, which has been described previously [10] and is composed of the following steps. Patients underwent standard retrobulbar anesthesia with the goal of complete akinesia of the globe within the orbit.…”
Section: Methods Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Current designs and techniques of radiation therapy need to be explored [16]. First studies on CyberKnife radiosurgery as a locoregional treatment for uveal melanoma showed promising results without serious acute adverse events [15,17].…”
Section: Introductionmentioning
confidence: 99%
“…Mit der Cyberknife-Therapie sind diese Schwachpunkte eliminiert. So ist eine superselektive Behandlung von Metastasen auch in bewegten Organstrukturen nach radiologisch interventioneller Platzierung eines Goldmarkers (fiducial) in einer einzigen ambulanten Bestrahlungsbehandlung ohne Fixierung des Patienten und mit lediglich minimaler Strahlenbelastung des umgebenden Gewebes möglich [24][25][26].…”
unclassified